2019
DOI: 10.3168/jds.2018-15423
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Purple corn (Zea mays L.) stover silage with abundant anthocyanins transferring anthocyanin composition to the milk and increasing antioxidant status of lactating dairy goats

Abstract: The present study used 16 multiparous lactating Saanen dairy goats (body weight, 41.80 ± 2.92 kg; mean ± standard deviation) with healthy and symmetrical udders. Goats were divided into 2 blocks of 8 goats based on milk yield averaged from 75 d in milk in a randomized completed block design. The 2 study groups were the control (CSSS), in which goats were fed sticky corn stover silage, and the treatment (TPSS), in which goats were fed anthocyanin-rich purple corn (Zea mays L.) stover silage (PSS). The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 13 publications
(15 reference statements)
5
32
0
2
Order By: Relevance
“…There were no changes (p > 0.05) in DM intake of BW kg/d and g/kg BW 0.75 among the four treatments. Even though anthocyanins are phenolic compounds that contribute to the characteristic bitter flavor of plants, results indicated that anthocyanin did not adversely affect cattle palatability [3]. This agreed with the results obtained by Hosoda [35], who reported that feeding with the purple pigment from anthocyanin-rich corn result in the same DM intake as the rice straw diet.…”
Section: Feed Utilization and Nutrient Digestionsupporting
confidence: 89%
See 1 more Smart Citation
“…There were no changes (p > 0.05) in DM intake of BW kg/d and g/kg BW 0.75 among the four treatments. Even though anthocyanins are phenolic compounds that contribute to the characteristic bitter flavor of plants, results indicated that anthocyanin did not adversely affect cattle palatability [3]. This agreed with the results obtained by Hosoda [35], who reported that feeding with the purple pigment from anthocyanin-rich corn result in the same DM intake as the rice straw diet.…”
Section: Feed Utilization and Nutrient Digestionsupporting
confidence: 89%
“…It was found that all nutrient digestibility was significant among treatments (p < 0.01). The increase in CP might have an effect on the high digestibility of purple field corn stover [3]. It could also be due to the high growth of mycelia in P. ostreatus and V. volvacea, which increased the protein concentration [37].…”
Section: Feed Utilization and Nutrient Digestionmentioning
confidence: 99%
“…6 Methionine mix containing (%): 2-hydroxy-4-(metylthio)butanoic acid, 40; MgO, 1.87. able for the last 4 wk (wk 9 to 12; Figure 1). These values were lower than the anthocyanin concentrations of purple corn silage reported in the literature: 0.34% of DM (Hosoda et al, 2009) and 862 mg/kg (Tian et al, 2019). However, our findings agreed with Hosoda et al (2009), who reported that the anthocyanin content of purple corn silage decreased during storage.…”
Section: Short Communicationsupporting
confidence: 67%
“…Natural food colors are found in fruits such as acai, cherries, cranberries, elderberries, raspberries, blueberries, black and blue grapes, plums, strawberries, figs, pomegranate, and red apple [12]. Other important sources are found in vegetables: beets, purple lettuce, green onion, radish, purple cabbage, red bell peppers, eggplant, as well as cereals such as blue corn (Zea mays L.) [13], blue wheat [14], and rice [15]. Recently, other plants and flowers have been studied as potential sources of antioxidants [16,17], such as elder (Sambucus nigra) [18], perilla fruit from Japan (Perilla frutescens) [19], and flower petals: iris (Iris dichotoma, Iris domestica) from China [20], Damascus rose (Rosa damascena) [21], cyani flower (Centaurea cyanus) [22], dahlia (Dahlia mignon) [23], and viola (Viola tricolor) [16].…”
Section: Anthocyanin Sourcesmentioning
confidence: 99%